Von der Blüte zum Honig - Mitgutsch, Ali 1935-2022 (Sellier, 1989)
Describes how honey is made, harvested and used.
Keywords: Jüdisches Krankenhaus Berlin; Geschichte 1933-1945; German language materials; Honey